ANALISA PENANGANAN KOMPLAIN PELANGGAN DI GO-KART LEMBANG SPEEDWAY - Ageng saepudin kanda S; Salma hasna hamidah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Research Method This research uses qualitative methods so that researchers are able to think and build their own knowledge. This research raises a deep phenomenon, until it finds logical answers from the research results and questions in the research. Based on the results of interviews conducted with the Go-Kart Lembang Speedway Owner and Lembang Speedway Go-Kart Supervisor as follows: Customer Complaints, Types of Customer Complaints, Causes of Customer Complaints, Customer Complaint Handling System, Benefits of Handling Complaints. So the researcher can draw the conclusion: Complaint handling at Go-Kart Lembang Speedway has been effective. Complaints submitted by customers at Go-Kart Lembang Speedway are regarding height and weight, queue line problems, customers who do not comply with regulations, expensive prices, In handling complaints at Go-Kart Lembang Speedway which acts as a media for customer complaints. Steps taken: receiving complaints, following up on complaints.